Catalytic combustion of a dendrimer containing ferrocene units with anti‐migration performance on composite propellant - Chen, Dingning; Yu, Haojie; Wang, Li; Vatsadze, Sergey Z.; Liu, Jinyi; Wang, Yu (Applied organometallic chemistry, 2023)
Ferrocene‐based compounds are promising burning rate catalysts due to their attractive catalytic activity, flammability, and non‐toxic performance. Unfortunately, the high‐migration issue of the ferrocene‐based catalysts makes it challenging to store composite solid propellants for a long time. Therefore, a dendrimer containing ferrocene units with anti‐migration ability was designed herein. The introduction of polar groups provides a large number of interaction sites for anti‐migration, and no migration of the dendrimer in the propellant was observed after 4 weeks of the aging test. For catalytic performance, the results showed that the thermal decomposition temperature of ammonium perchlorate could be reduced from 404°C to 369°C by adding 3 wt% ferrocene‐based dendrimer. Moreover, compared with the propellant mixed with Catocene, the propellant containing ferrocene‐based dendrimer showed a lower pressure exponent (0.47) and a higher burning rate (2.03 mm·s−1, at 0.1 MPa). A new dendrimer containing ferrocene units is used as an efficient combustion catalyst for ammonium perchlorate‐based propellant.